Keterkaitan Sustainability Report, Kesetaraan Gender, Earning Per Share terhadap Harga Saham Perdana - Victoria Ari Palma Akadiati (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
Abstract. The purpose of this study is to empirically analyze the effect of sustainability report, gender equality, and earnings per share on the initial share price of initial public offering companies in 2022. Research is quantitative with research methods using purposive sampling techniques with multiple linear progression data analysis. The results showed that the sustainability report had no influence on the initial share price. Gender equality and earnings per share have a significant influence on the initial share price. The importance of stock prices in a company can be used as a tool to measure company performance in predicting returns and mitigating risk in the sustainable future. The implications of the results of this study can be used as literacy for subsequent research and as a consideration for interested parties in making decisions to invest in shares in the Indonesian stock exchange market.